2009
DOI: 10.1037/a0015302
|View full text |Cite
|
Sign up to set email alerts
|

Targeting children's behavior problems in preschool classrooms: A cluster-randomized controlled trial.

Abstract: The present study evaluated the efficacy of a multicomponent, classroom-based intervention in reducing preschoolers' behavior problems. The Chicago School Readiness Project model was implemented in 35 Head Start classrooms using a clustered-randomized controlled trial design. Results indicate significant treatment effects (ds = 0.53-0.89) for teacher-reported and independent observations of children's internalizing and externalizing behavior problems. Moreover, there was some evidence for the moderating role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
234
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(249 citation statements)
references
References 61 publications
12
234
1
2
Order By: Relevance
“…Our meta-study, however, included two studies (Benner, Nelson, Sanders, & Ralston, 2012;Raver et al, 2009) in which these were reported for behavioral outcomes, and both came to an average value of 0.1. This is also the value used in the meta-analyses of What Works Clearinghouse (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-study, however, included two studies (Benner, Nelson, Sanders, & Ralston, 2012;Raver et al, 2009) in which these were reported for behavioral outcomes, and both came to an average value of 0.1. This is also the value used in the meta-analyses of What Works Clearinghouse (2014).…”
Section: Discussionmentioning
confidence: 99%
“…A few randomized trials or natural experiments have shown that lower barriers to education and some early childhood programs have economic and health benefits. [9][10][11] Despite recent education reform efforts in the United States, whether better health can be achieved through public education improvements is unproven.…”
Section: Discussionmentioning
confidence: 99%
“…Though numerous empirically tested programmes successfully alter or deflect young children's development of DBPs (e.g. Raver et al 2009;Webster-Stratton and Reid 2010), few programmes have targeted the transition to kindergarten or issues specific to this adaptation period, in spite of the fact that this may be a period may be where improvements can have a particularly long-lasting impact (Pianta and Rimm-Kaufman 2006). As an indicated prevention programme -in other words, one that is designed for individuals with early signs of the targeted problem -Starting Strong targets children who already show DBPs in school or those with early risk for DBPs during the transition to school.…”
Section: The Interventionmentioning
confidence: 99%